Politeness and Appropriateness in Physiotherapist-Patient Communication - Kusnaeni, Santhy Ria; Ekarina, Ekarina (Universitas Cokroaminoto Palopo, 2026)
This article investigates the notion of appropriateness and politeness in healthcare communication. Interactions in healthcare, especially in physiotherapy treatment often require complex politeness strategies where strict instructions must be balanced with care and collaboration. This situation presents a communicative challenge for many healthcare professionals who might not have been trained in communication strategies. To understand these communication dynamics better, this article sets out to understand: (1) what language forms are used to negotiate instructions between physiotherapists and patients during assessment; and (2) how politeness is discursively constructed by physiotherapists during assessment interactions. To do this, the authors analyzed data from a YouTube video that contains a functional physiotherapy assessment between a therapist and a patient. The video was transcribed and coded to identify sentence types used by the therapist, as well as the functions of those sentences. Selected sequences were then analyzed to understand the negotiation of appropriateness in the local context (Locher and Watts, 2005). Our results uncover that interrogatives are the most frequently used sentence type by the physiotherapist. However, the language forms cannot be cleanly mapped to function; for example, instruction-giving was realized across all sentence types: interrogatives, declaratives and imperatives. Instead, appropriateness and politeness were achieved through interactional practices involving collaboration, uptake, ratification and accommodation between the physiotherapist and the patient.